Lessons in Effector and NLR Biology of Plant-Microbe Systems - Białas, Aleksandra; Zess, Erin K.; De la Concepcion, Juan Carlos; Franceschetti, Marina; Pennington, Helen G.; Yoshida, Kentaro; Upson, Jessica L.; Chanclud, Emilie; Wu, Chih-Hang; Langner, Thorsten; Maqbool, Abbas; Varden, Freya A.; et al. (Molecular plant-microbe interactions, 2018)
A diversity of plant-associated organisms secrete effectors—proteins and metabolites that modulate plant physiology to favor host infection and colonization. However, effectors can also activate plant immune receptors, notably nucleotide-binding domain and leucine-rich repeat region (NLR)-containing proteins, enabling plants to fight off invading organisms. This interplay between effectors, their host targets, and the matching immune receptors is shaped by intricate molecular mechanisms and exceptionally dynamic coevolution. In this article, we focus on three effectors, AVR-Pik, AVR-Pia, and AVR-Pii, from the rice blast fungus Magnaporthe oryzae (syn. Pyricularia oryzae), and their corresponding rice NLR immune receptors, Pik, Pia, and Pii, to highlight general concepts of plant-microbe interactions. We draw 12 lessons in effector and NLR biology that have emerged from studying these three little effectors and are broadly applicable to other plant-microbe systems.